2004
DOI: 10.1038/sj.ejhg.5201250
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA mutations in patients with postlingual, nonsyndromic hearing impairment

Abstract: Mitochondrial mutations have previously been reported anecdotally in families with maternally inherited, nonsyndromic hearing impairment. To ascertain the contribution of mitochondrial mutations to postlingual but early-onset, nonsyndromic hearing impairment, we screened patients collected from within two different populations (southern Italy and UK) for previously reported mtDNA mutations associated with hearing disorders. Primer extension (SNP analysis) was used to screen for specific mutations, revealing ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 47 publications
(50 reference statements)
1
61
0
3
Order By: Relevance
“…The m.7510T>C mtDNA mutation was not detected in normal Caucasian controls (Hutchin et al 2000), nor in haplogroup-or sub-haplogroupmatched controls (Labay et al 2008). Although it was not found in some large screening populations with nonsyndromic SNHL (Jacobs et al 2005;Lévêque et al 2007), several families have already been described.…”
Section: Introductionmentioning
confidence: 98%
“…The m.7510T>C mtDNA mutation was not detected in normal Caucasian controls (Hutchin et al 2000), nor in haplogroup-or sub-haplogroupmatched controls (Labay et al 2008). Although it was not found in some large screening populations with nonsyndromic SNHL (Jacobs et al 2005;Lévêque et al 2007), several families have already been described.…”
Section: Introductionmentioning
confidence: 98%
“…Most individuals carrying this mutation had progressive SNHL, and some of them were accompanied by a widespread neurological disease including ataxia, dysarthria, and myoclonic seizures. This mutation was later found in a large Dutch family [46] and in several sporadic subjects with nonsyndromic hearing loss [47]. In the Dutch family, the hearing loss is sensorineural progressive with onset in early adulthood, and only a single family member with hearing loss showed accompanying neurological symptoms.…”
Section: Mitochondrial Trna Mutations Associated With Nonsyndromic Hementioning
confidence: 93%
“…In the mitochondrial tRNA Ser(UCN) gene, five nonsyndromic deafness-associated mutations, A7445G [42][43][44], 7472insC [45][46][47], T7510C [48,84], T7511C [49][50][51][52][53], and G7444A [55][56][57], have been found in families from various ethnic backgrounds. These mutations often occur in homoplasmy or in high levels of heteroplasmy, indicating a high threshold for pathogenicity.…”
Section: Mitochondrial Trna Mutations Associated With Nonsyndromic Hementioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that mutation m.1494C>T might associate with aminoglycoside-induced hearing loss in a large Chinese family [8,10,11]., while the mutation m.1555A>G may contribute to both aminoglycoside-induced and nonsyndromic hearing loss in families worldwide [12,13]. Both m.1555A>G and m.1494C>T mutations locate in a highly conserved region of 12SrRNA that is implicated in aminoglycoside binding in bacteria.…”
mentioning
confidence: 99%